Penyelesaian Permasalahan Multi-tour Inventory Routing Problem dengan Particle Swarm Optimization - Budiman, Syarif Daniel; Widyadana, I Gede Agus (Jurnal Titra, 2013)
The Inventory Routing Problem (IRP) has become a problem that thoroughly studied recently. One of the IRP models that have been developed was an IRP multi-tour, which described a single distribution center r with a set of salespoints. The salespoints is served by a limited number of vehicles with finite load capacities. Vehicle will replenish the salespoints by making a multi-tour route. Each multi-tour consists of a set of sub-tour involving salespoints to be replenished. The multi-tour solution has increase the complexity of the model compared to the normal tour IRP model. Therefore a Particle Swarm Optimization (PSO) algorithm has been proposed for solving a sequential problem in allocating salespoints to the route. Some heuristic methods also been developed for creating the multi-tour. The validity of the algorithm, along with comparison with other existing algorithm, has been provided to validate the proposed PSO algorithm. Result obtained has shown that the PSO algorithm having a promising performance in solving the problem.